Shifting contexts, shifting identities: a realist exploration of transnational mobility, change and identity construction in South African Higher Education expatriates in Abu Dhabi, UAE. - Reid, Gillian Janet (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2019)
Positioned in relation to the globalization of higher education, this realist study is approached from an interest in identity and focuses on nine South African academics professional contexts in South Africa and Abu Dhabi, UAE. As the context of identity formation and emergence is always local, the intention of this research was never to generalize. Rather, in using Bhaskar's critical realism as its underpinning philosophy, and Archer's social realism, theories on self, personal and the development and attainment of social identity - her concept of analytical dualism and her morphogenetic framework, this qualitative case study was designed to explore how global and national powers and mechanism effected change in this sub-group of academic's respective higher education sectors and institutions in post- 1994 South Africa and in Abu Dhabi between 2008 and 2016. The study suggests that participants perceived their academic roles and role-incumbent professional identities to have been negatively impacted by the changes that were implemented in the South African higher education sector as a result the countries reintroduction to the global stage. Their response to become transnational educators in Abu Dhabi's presented them with conditions that allied their professional experiences of the transformation of South African's higher education sector. This led to a continued sense of loss of academic agency and powerlessness. This effecting the emergence, through the personal power of reflectivity, combined with discourse and affinity powers and mechanisms, in a social identity that supplanted their academic identities.
Keywords: College teacher mobility; College teacher mobility -- AbuÌ„ ZÌ£aby (United Arab Emirates); College teachers, Foreign -- AbuÌ„ ZÌ£aby (United Arab Emirates); College teachers -- Psychology; Expatriation -- Psychological aspects